Creating transnational social spaces - Ješe Perković, Ana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2024)
The article addresses the topic of transnational social spaces through a study of the activities of migrants’ descendants. In this qualitative research, we conducted interviews with the descendants of the immigrant community from Bosnia and Herzegovina in Slovenia to examine how they maintain transnational ties with extended kinship and leverage the benefits of these networks. Through interview excerpts, we present the mechanism of reciprocity, descendants’ involvement in institutional, organisational, and business cooperation within broader transnational networks, and their modes of communication with the transnational kinship group.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; descendants; immigrants; potomci; priseljenci; Slovenia; Slovenija; transnacionalni družbeni prostori; transnational social spaces